Strain differentiation of foot-and-mouth disease virus type 'Asia 1' - MISHRA, N; RAI, D V; PATTNAIK, B P (The Indian Journal of Animal Sciences, 2013)
Foot-and-month disease (FMD) Virus isolates(20) of serotype'Asia1'isplated from outbreaks during 1987-92 from different parts of India were analyzed to assess their relationship with the Asia 1 vaccine strain virus in micro-complement fixation test (CFT), sandwich enzyme-linked iminunosorbent assay (ELISA) and 2-dimensional miero-neutali/ation test(2D-MNT) using anti-1468 gunicapig serum raised against the vaccine stain virus. In micro-CFT the relationship (rvalue) of the field isolated with the vaccine strain virus ranged from 0.5 to 0.75. In sandwich ELISA,1 isolates showed r values in the range of 0.75 to 1.00.7 isolates gave values in the range of 0.50 to 0.74 and 0 isolates gave somewhat lower r values (r=0.44_. In 2D-Mnt, 11 isolates gave r values of 1.00 and remaining 9 islates gave r values between 0.51 and 0.91. All the field isolates were thus related to the vaccine strain virus. There was no significant difference between r values obtained with sandwich ELISA and 2D-MNT.